PENGARUH PERNIKAHAN DINI TERHADAP KEHARMONISAN PASANGAN SUAMI DAN ISTRI DI DESA BAGAN BHAKTI KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR - Eka Rini Setiawati; T.Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Early marriage is a marriage under the age or younger age that should not yet ready to marriage. Normal marriage age limit is based on healty marriage age is 20 years of age for women and 25 years for men. This study airms ti determine the effect of early marriage on the level of harmony and also know the effect of the implementation of family functiontioning in couples who married in early age. The research using the theory of deviant behavior, juvenile delinquency and social control. The research method is quanlitative descriptive. To finds out the result the author using, koesioner, observation technique, interviews and documentation. This research subjects selected by purposive sampling .. As the result of all the 30 Respondents mostly had a low level of harmonization of family functioning that has not done well.Keywords : Early marriage, family fungtion, family harmony.